Солевая чувствительность и сахарный диабет - Hovaka, V.V.; Korpacheva-Zinych, L.V.; Kushnareva, N.N.; Gritsenko, E.N.; Korpachev, V.V. (Ендокринологія | Endokrynologia, 2020)
Солевая чувствительность и сахарный диабет